2001
DOI: 10.1002/jmri.1182
|View full text |Cite
|
Sign up to set email alerts
|

MRI of carcinoid tumors: Spectrum of appearances in the gastrointestinal tract and liver

Abstract: The purpose of this study was to evaluate the spectrum of appearances of gastrointestinal carcinoid tumors at magnetic resonance imaging (MRI) and to elucidate patterns of appearances of carcinoid liver metastases on precontrast and postgadolinium images. The MR examinations of 29 patients (11 men, 18 women; age range, 33-87 years) with histologically confirmed gastrointestinal carcinoid tumors, representing our complete 9.5 years of experience with this entity, were retrospectively reviewed. Twelve patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 27 publications
0
73
0
4
Order By: Relevance
“…Similarly, hepatic metastases are well depicted on MRI, and MRI is often used to further characterize lesions that are equivocal on CT. Like the primary lesions, hepatic metastases appear as T1 hypointense and T2 hyperintense. Bader et al [36] showed this finding in 75% of cases. Interestingly, 15% of cases showed increased enhancement only in the arterial phase.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, hepatic metastases are well depicted on MRI, and MRI is often used to further characterize lesions that are equivocal on CT. Like the primary lesions, hepatic metastases appear as T1 hypointense and T2 hyperintense. Bader et al [36] showed this finding in 75% of cases. Interestingly, 15% of cases showed increased enhancement only in the arterial phase.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 83%
“…Gastrinomas tend to show ring or peripheral enhancement while most other subtypes of NETs demonstrated a diffuse pattern of enhancement. For GI NETs, MRI is able to detect around two-thirds of lesions [36] , with fat-suppressed T1W imaging yielding maximal results. Similarly, hepatic metastases are well depicted on MRI, and MRI is often used to further characterize lesions that are equivocal on CT. Like the primary lesions, hepatic metastases appear as T1 hypointense and T2 hyperintense.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…(Pilichowska et al, 1999;Modlin et al, 2008;Yao et al, 2008;Zeng et al, 2013). Liver neuroendocrine carcinoma found in clinical mostly induced by the intestines and pancreas transfer, PHNEC was very rare originating in the liver (Pilichowska et al, 1999;Tohyama et al, 2005;Hamanaka et al, 2012;Yalav et al, 2012), accounting for 1%-5% of all liver cancer, and 0.8% -4.0% of systemic neuroendocrine tumors, the imaging findings were lack of specificity, leading to difficultly preoperative diagnosis (Pilichowska et al, 1999;Bader et al, 2001;Tohyama et al, 2005;Ulusan et al, 2005;Krohn et al, 2011;Yalav et al, 2012;Baek et al, 2013). Patients generally did not have carcinoid syndrome and were lack of specific clinical symptoms and signs.…”
Section: Discussionmentioning
confidence: 99%
“…Primary liver cell neuroendocrine carcinoma was a rare primary liver cancer, the imaging performance was still lack of awareness and understanding, resulting in often misdiagnosis (Bader et al, 2001;Ulusan et al, 2005;Rufini et al, 2006;Krohn et al, 2011;Baek et al, 2013;Li et al, 2013). The main differential diagnosis was primary hepatocellular carcinoma and bile duct carcinoma (Kim et al, 2011;Yalav et al, 2012;Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation